2022
DOI: 10.1039/d1tc05270e
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing near-infrared lightviaS0to T1sensitizer excitation in a molecular photon upconversion solar cell

Abstract: Integrating molecular photon upconversion via triplet-triplet annihilation (TTA-UC) driectly into a solar cell offers a means of harnessing sub-bandgap, near infrared (NIR) photons and surpassing the Shockley-Quessier limit. However, all...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…This approach has two advantages: this bypasses the problem of limited triplet exciton diffusion, and direct electron injection bypasses UC emission-solar cell reabsorption losses . Important demonstrations using TTA-UC have been reported for dye-sensitized solar cells using solution-based electrolytes. Still, moving toward solid-state device architectures is highly advantageous for scalability and durability. This is recently exemplified by the boon in perovskite solar cell research and commercialization which originated from the dye-sensitized solar cell community, with the transition to a fully solid-state device architecture serving as a key enabling technological innovation. , Recently, the Rand group engineered a solid-state “intermediate band solar cell”, whereupon PtTPTBP sensitized the annihilator (α-sexithiophene) with triplets.…”
Section: Solid-state Applicationsmentioning
confidence: 99%
“…This approach has two advantages: this bypasses the problem of limited triplet exciton diffusion, and direct electron injection bypasses UC emission-solar cell reabsorption losses . Important demonstrations using TTA-UC have been reported for dye-sensitized solar cells using solution-based electrolytes. Still, moving toward solid-state device architectures is highly advantageous for scalability and durability. This is recently exemplified by the boon in perovskite solar cell research and commercialization which originated from the dye-sensitized solar cell community, with the transition to a fully solid-state device architecture serving as a key enabling technological innovation. , Recently, the Rand group engineered a solid-state “intermediate band solar cell”, whereupon PtTPTBP sensitized the annihilator (α-sexithiophene) with triplets.…”
Section: Solid-state Applicationsmentioning
confidence: 99%
“…In 2022, Beery et al reported a TET rate between the sensitizer and the acceptor to be around 4−5 × 10 8 s −1 , where a lower redox mediator concentration, compared to what we used herein, was used. 91 This explains the significant quenching of the PtTBTPP phosphorescence in the case of using the Co 2+/3+ and I − /I 3 − mediators, compared to when using the TPAA 0/+ mediator, which has a 3 orders of magnitude lower quenching rate. Additionally, after measuring the oxidation and reduction potentials (using the cyclic voltammetry, see Section S1.3 in Supporting Information) of the dyes and redox mediators employed in this study, and as shown in Figure 6, the driving force of the electron transfer between the three mediators and the PtTBTPP sensitizer was then calculated.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The TiO 2 -PBPEA-Zn-Os bilayered DSSC with I 3 -/3Ias redox mediator showed ∆𝐽 sc ~ 3.5 µA cm -2 under AM 1.5 solar excitation. 110 The low ∆𝐽 sc despite broad absorption range was attributed to slow Please do not adjust margins Please do not adjust margins sensitizer to annihilator triplet energy transfer, a low injection yield for the annihilator, and fast back energy transfer from the upconverted state to the sensitizer. 110 To avoid the sensitizer's aggregation on the annihilator-TiO 2 film Nagata's research group co-adsorbed the sensitizer (PtTPO) on TiO 2 with a long alkyl chain spacer (Fig.…”
Section: Materials Chemistry Frontiers Accepted Manuscriptmentioning
confidence: 99%